Anomalous muon magnetic moment, supersymmetry, naturalness, LHC search limits and the landscape - Howard Baer; Vernon Barger; Hasan Serce (Physics Letters B, 2021)
The recent measurement of the muon anomalous magnetic moment aμ≡(g−2)μ/2 by the Fermilab Muon g−2 experiment sharpens an earlier discrepancy between theory and the BNL E821 experiment. We examine the predicted Δaμ≡aμ(exp)−aμ(th) in the context of supersymmetry with low electroweak naturalness (restricting to models which give a plausible explanation for the magnitude of the weak scale). A global analysis including LHC Higgs mass and sparticle search limits points to interpretation within the normal scalar mass hierarchy (NSMH) SUSY model wherein first/second generation matter scalars are much lighter than third generation scalars. We present a benchmark model for a viable NSMH point which is natural, obeys LHC Higgs and sparticle mass constraints and explains the muon magnetic anomaly. Aside from NSMH models, then we find the (g−2)μ anomaly cannot be explained within the context of natural SUSY, where a variety of data point to decoupled first/second generation scalars. The situation is worse within the string landscape where first/second generation matter scalars are pulled to values in the 10−50 TeV range. An alternative interpretation for SUSY models with decoupled scalar masses is that perhaps the recent lattice evaluation of the hadronic vacuum polarization could be confirmed which leads to a Standard Model theory-experiment agreement in which case there is no anomaly.